Quantifying Fiscal Multipliers in South Africa: A Structural Var Approach - Ntshangase, Lwazi Senzo; Ngozo, Thando (Journal of Economics and Behavioral Studies, 2024)
Fiscal multipliers have deteriorated in South Africa since the global financial crisis in 2008 and 2009. Weakening fiscal multipliers to a record low of zero has constrained the government’s ability to use fiscal policy measures to stimulate the economy, particularly in the aftermath of the COVID-19 pandemic and recent geopolitical risks affecting the global economy. The current paper quantifies fiscal multipliers in South Africa. The study employed the structural vector autoregressive to quantify government spending and government tax revenue fiscal multipliers in South Africa over the period 2000M01–2023M10. The control variables for the study are government total spending, total government tax revenue, and the production index as a proxy variable for economic activity. This is the first study to employ high-frequency monthly data, which increases the number of observations, thus yielding significant and robust results. The accumulated government expenditure and government tax revenue multipliers are 0.4 and 0.1, respectively. The empirical results are consistent with the Keynesian view that government spending, particularly investment spending, fosters economic growth. Structural reforms in logistics, the energy sector, and education to boost economic growth and improve fiscal multipliers that are currently less than one in South Africa must be adopted as a policy response.